(untitled) (Nonconventional Technologies Review, 2019)
This paper is about the manufacturing process of a rim from aluminum alloy after the molding process. We describe the deburring process with laser cutting machine, surface finishing with vibration and establish the critical points on an eventual impact on a car rim. The wheel impact test evaluates the wheel structural performance for a typical impact event occurring in passenger cars. The basic design of the study is built upon the development and model optimization of car rims. This impact test performance is critical to meeting overall structural performance for the wheel. Discoveries found as a result of our analysis is the improved method which closely captures the behavior of the wheel during and after impact and the designing of wheel geometry which enhances the stability of a car in case of an accident. The paper is presenting the optimal design for car wheels. The final goal of this research is to have safer cars to drive and to create a wheel that is strong enough to resist to major deformations in case of a frontal impact at a high force.